Flow Behaviour of Inhaled Fibres – Equations of Motion and Preliminary Results of Real Trajectories Recorded by a High-Speed Camera - Lízal, František; Bělka, Miloslav; Malý, Milan; Cabalka, Matouš; Jedelský, Jan; Jícha, Miroslav (EDP Sciences, 2020)
The ability to precisely predict the fate of inhaled fibres is important for toxicologists as well as for pharmaceutists struggling to utilize fibres as carriers of a medication. However, the complexity of fibre movement in human airways still represents a significant challenge for programmers of codes for simulation of fibre flow. This conference contribution introduces the theoretical equations of fibre motion which can be used for calculation of the fate of inhaled fibres, and also, in the second part, first results of high-speed camera recorded trajectories of fibres downstream of a realistic human airway bifurcation are presented as an illustration of the real behaviour of fibres in the lungs.

The ability to precisely predict the fate of inhaled fibres is important for toxicologists as well as for pharmaceutists struggling to utilize fibres as carriers of a medication. However, the complexity of fibre movement in human airways still represents a significant challenge for programmers of codes for simulation of fibre flow. This conference contribution introduces the theoretical equations of fibre motion which can be used for calculation of the fate of inhaled fibres, and also, in the second part, first results of high-speed camera recorded trajectories of fibres downstream of a realistic human airway bifurcation are presented as an illustration of the real behaviour of fibres in the lungs.
Flow Behaviour of Inhaled Fibres – Equations of Motion and Preliminary Results of Real Trajectories Recorded by a High-Speed Camera
Keywords: fibres; airway; motion; high-speed camera; fibres; airway; motion; high-speed camera